2022
DOI: 10.1167/iovs.63.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Axial Elongation During Short-Term Accommodation in Myopic and Nonmyopic Children

Abstract: Purpose Axial length increases during accommodation in adults and children; however, refractive error group differences are conflicting and have not been explored in pediatric populations. This study aimed to evaluate differences in accommodation-induced axial elongation between myopic and nonmyopic children. Methods A range of ocular biometric measurements were captured during brief accommodation tasks (0, 3, 6, and 9 D) using a Badal optometer mounted to a noncontact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Children use short working distances, 41,42 particularly when using screen devices 43 . An accommodative demand over 6D is associated with axial elongation, 44 and 6‐ to 8‐year‐old children appear to be more susceptible to environmental changes than older children 15 . Prior research revealed faster axial elongation between 8 and 11 years of age and slowing between the ages of 13–16 years 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Children use short working distances, 41,42 particularly when using screen devices 43 . An accommodative demand over 6D is associated with axial elongation, 44 and 6‐ to 8‐year‐old children appear to be more susceptible to environmental changes than older children 15 . Prior research revealed faster axial elongation between 8 and 11 years of age and slowing between the ages of 13–16 years 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in other ocular components could also contribute to the short-term axial length change. Hughes reported that anterior chamber depth (ACD), crystalline lens thickness (LT), anterior segment length (ASL), and vitreous chamber depth (VCD) altered significantly during accommodation, resulting in an increment in axial length [10]. Moreover, such changes were more prominent in the myopic group and existed in adults and children [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Hughes reported that anterior chamber depth (ACD), crystalline lens thickness (LT), anterior segment length (ASL), and vitreous chamber depth (VCD) altered significantly during accommodation, resulting in an increment in axial length [10]. Moreover, such changes were more prominent in the myopic group and existed in adults and children [10][11][12]. Whether short-term RLRL treatment can cause changes in anterior segment parameters in myopic adults is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Obwohl zuverlässige Daten zu Bildschirmzeit oder verwendeten Abständen für große Kohorten fehlen, sollte neben Abständen auch an regelmäßige Pausenzeiten erinnert werden. Möglicherweise handelt es sich bei der akkommodationsassoziierten Progression um einen Mechanismus, der insbesondere bei einer bereits bestehenden Myopie zum Tragen kommt [ 21 ]. Lesezeiten von über 30 min bei weniger als 30 cm Leseabstand sollten durch 10 min Blick in die Ferne unterbrochen werden.…”
Section: Beratung Zu Verhalten Und Präventiven Maßnahmenunclassified